2013
DOI: 10.1111/j.2047-3095.2013.01239.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Educational Program on the Use of Standardized Nursing Languages for Nursing Documentation Among Public Health Nurses in Nigeria

Abstract: Educating PHNs and providing them with standardized nursing care plans enhance documentation of care. IMPLICATION TO PRACTICE: A combination of education on the use of standardized nursing languages and standardized nursing care plans can enhance documentation of care. There is a need for more research on the use of standardized nursing languages in developing nations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 14 publications
7
20
0
Order By: Relevance
“…Items 12 and 16 can be discussed under the same perspective, since both address issues fundamental for nursing care and documentation: the description of the problem and the signs/symptoms. However, these items would only receive maximum scores if their records were in accordance with NANDA-I 8 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Items 12 and 16 can be discussed under the same perspective, since both address issues fundamental for nursing care and documentation: the description of the problem and the signs/symptoms. However, these items would only receive maximum scores if their records were in accordance with NANDA-I 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation started in the first record (admission or first evolution). This period is determined according to the recommendations of the Quality of Diagnosis, Interventions and Outcomes (Q-DIO) 7 - 8 . There was no collection of patient information, such as age or diagnosis, and there were no interviews, since those were not the focus of the study or part of the instrument items.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They reported a statistically significant improvement in their pain assessment and management practice after the implementation of the program with the p=0.004, 0.17 respectively as opposed to a study by Kaur (2017), on knowledge and attitude regarding pain management among staff nurses at Kular Hospital, Bija (Punjab), where nurse were reported to have average knowledge and attitudes towards pain management. Furthermore, in a related study by Odutayo et al (2013), on impact of an educational program on the use of standardized nursing languages for nursing documentation among public health nurses in Nigeria, a significant difference with the t value = -27.61, d.f. 99, p = 0.0001 in the mean score of pretest and posttest of their experimental group was reported which also revealed that knowledge was impacted.…”
Section: Parametermentioning
confidence: 99%